Problem Teologis Ideologi Komunisme - Muhamad Yakub Mubarok (Universitas Darussalam Gontor, 2017)
It is known that the communism had affected the history of this world. This ideology had succeeded influencing a third of the world in less than one century after Karl Marx’s death and it had caused some revolutionary movements at some countries of the world. It is interesting to say that even what Marx had predicted about the history of human being in the future was not surely proven, but his ideas have been affecting people. But, the communism has serious problems related to the theological matter for sure. It could make people becoming atheist. Moreover, it could create the people hate their religion, but they could become religion’s antagonists. Marx’s hatred toward religions was expressed by the words: “Religion is the opium of the masses”. Then Lenin, another figure of the communism, did a discrimination to religious people, as well as, Joseph Stalin and Mao Zedong who prohibited all kinds of religious activities during their lifetime. Long time ago, thousands of Indonesian Moslems were becoming victims of a communist party in Indonesia (PKI). Nowadays, the communism doctrine begins to appear and affect some youths of Indonesia. Perhaps, it does because they have been frustrated and being disappointed by the socio-political condition which is controlled by modern capitalists. But, they have to be aware that the communism is not a solution. In fact, it is surely dangerous. It could ruin religions’ concepts. Hence, this article would try to explain some theological problems of the communism ideology.